Variation in enamel thickness within the genus Homo - Smith, Tanya M.; Glasmacher, Ulrich A. (Journal of human evolution, 2012)
Recent humans and their fossil relatives are classified as having thick molar enamel, one of very few dental traits that distinguish hominins from living African apes. However, little is known about enamel thickness in the earliest members of the genus Homo, and recent studies of later Homo report considerable intra- and inter-specific variation. In order to assess taxonomic, geographic, and temporal trends in enamel thickness, we applied micro-computed tomographic imaging to 150 fossil Homo teeth spanning two million years. Early Homo postcanine teeth from Africa and Asia show highly variable average and relative enamel thickness (AET and RET) values. Three molars from South Africa exceed Homo AET and RET ranges, resembling the hyper thick Paranthropus condition. Most later Homo groups (archaic European and north African Homo, and fossil and recent Homo sapiens) possess absolutely and relatively thick enamel across the entire dentition. In contrast, Neanderthals show relatively thin enamel in their incisors, canines, premolars, and molars, although incisor AET values are similar to H. sapiens. Comparisons of recent and fossil H. sapiens reveal that dental size reduction has led to a disproportionate decrease in coronal dentine compared with enamel (although both are reduced), leading to relatively thicker enamel in recent humans. General characterizations of hominins as having ‘thick enamel’ thus oversimplify a surprisingly variable craniodental trait with limited taxonomic utility within a genus. Moreover, estimates of dental attrition rates employed in paleodemographic reconstruction may be biased when this variation is not considered. Additional research is necessary to reconstruct hominin dietary ecology since thick enamel is not a prerequisite for hard-object feeding, and it is present in most later Homo species despite advances in technology and food processing.
Gesehen am 09.07.2019